2019
DOI: 10.1021/acs.joc.9b01921
|View full text |Cite
|
Sign up to set email alerts
|

C–N Coupling via Antiaromatic Endocyclic Nitrenium Ions

Abstract: Herein, we report a C–N coupling reaction via antiaromatic endocyclic nitrenium ions. The nitrenium ion intermediate was generated by a combination of iodine­(III) reagent PhI­(OCOCF3)2 and the N–H center of benzimidazole units at ambient laboratory conditions. Metal-free synthesis of benzimidazole-fused phenanthridine derivatives was achieved in good to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 52 publications
(90 reference statements)
0
39
0
Order By: Relevance
“… 94 † Importantly, this approach is not limited to the oxidation of carboxamides, but can be similarly applied to nitrogen atoms in benzimidazoles. 162 α-Tertiary amines may undergo a 1,2-alkyl shift onto the nitrenium species. The thus generated iminium ion can be subsequently trapped by sodium cyanoborohydride as the secondary nucleophile.…”
Section: Cross-nucleophile Coupling Using Iodine( III )mentioning
confidence: 99%
See 1 more Smart Citation
“… 94 † Importantly, this approach is not limited to the oxidation of carboxamides, but can be similarly applied to nitrogen atoms in benzimidazoles. 162 α-Tertiary amines may undergo a 1,2-alkyl shift onto the nitrenium species. The thus generated iminium ion can be subsequently trapped by sodium cyanoborohydride as the secondary nucleophile.…”
Section: Cross-nucleophile Coupling Using Iodine( III )mentioning
confidence: 99%
“… † Importantly, this approach is not limited to the oxidation of carboxamides, but can be similarly applied to nitrogen atoms in benzimidazoles. 162 …”
Section: Cross-nucleophile Coupling Using Iodine( III )mentioning
confidence: 99%
“…Recently in 2019, Mal and co‐workers disclosed a metal‐free C−N coupling reaction to construct various benzimidazole‐fused phenanthridine derivatives 338 through a nitrenium ion intermediate using readily available iodine(III) reagent PhI(OCOCF 3 ) 2 [101] . This C−N cross‐coupling reaction has avoided inexpensive catalysts and harsh conditions.…”
Section: Synthesis Of Phenanthridinesmentioning
confidence: 99%
“…Recently in 2019, Mal and co-workers disclosed a metal-free C À N coupling reaction to construct various benzimidazole-fused phenanthridine derivatives 338 through a nitrenium ion intermediate using readily available iodine(III) reagent PhI(OCOCF 3 ) 2 . [101] This CÀ N cross-coupling reaction has avoided inexpensive catalysts and harsh conditions. Additionally, ambient conditions and commercially available iodine reagent made this synthetic protocol more attractive towards the construction of heterocycles (Scheme 119).…”
Section: Using Iodonium Saltsmentioning
confidence: 99%
“…Mal et al reported the use of PIFA (PhI(OCOCF 3 ) 2 ) for six-membered aromatic substitutions via a proposed nitrenium ion intermediate ( Scheme 36 a) [ 112 ]. Cho et al made the reaction at N -1 of benzimidazole intermolecular, with addition onto aryl isocyanate and aromatic substitution of the carbamoyl-NH to give fused quinazolinones and pyrimidinones ( Scheme 36 b) [ 113 ].…”
Section: Syntheses Of Ring-fused Benzimidazoles and Imidazobenzimidazolesmentioning
confidence: 99%